2020
DOI: 10.1002/hbe2.232
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing pathogens: Disfluent shapes of pathogens increase their perceived complexity and danger while realism and disfluency boost the credibility of visualizations

Abstract: During the COVID‐19 pandemic, the public was regularly presented with visualizations of the viral pathogen causing this disease. Since there are several ways of visually communicating information, we investigate whether different types of visualizations affect how viewers judge the credibility of information as well as the complexity and potential harm of pathogens. A first experiment was conducted to assess whether a round, fluent shape elicits a different response than pathogens featuring disfluent component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For instance, a recent study found that even minor changes in the (visual) presentation of pathogens can have a substantial effect. The subjective level of danger felt when being presented with visualizations of pathogens can be affected by their shapes (Skulmowski & Rey, 2020b). As the type of visualization used to accompany information on pathogens can thus potentially contribute to a heightened level of anxiety, the mere selection of graphics that are used in a news report becomes a task with a high responsibility (Skulmowski & Rey, 2020b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a recent study found that even minor changes in the (visual) presentation of pathogens can have a substantial effect. The subjective level of danger felt when being presented with visualizations of pathogens can be affected by their shapes (Skulmowski & Rey, 2020b). As the type of visualization used to accompany information on pathogens can thus potentially contribute to a heightened level of anxiety, the mere selection of graphics that are used in a news report becomes a task with a high responsibility (Skulmowski & Rey, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…The subjective level of danger felt when being presented with visualizations of pathogens can be affected by their shapes (Skulmowski & Rey, 2020b). As the type of visualization used to accompany information on pathogens can thus potentially contribute to a heightened level of anxiety, the mere selection of graphics that are used in a news report becomes a task with a high responsibility (Skulmowski & Rey, 2020b). Considering the highly emotional responses in the first wave (e.g., Su, Wu, Li, Xue, & Zhu, 2021), the aspect of how and at which rate information is conveyed to the public during such long emergency situations needs to be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the credibility of learning content is a highly relevant factor for educational contexts (Chinn et al, 2020;Scharrer et al, 2019). The stronger resemblance between realistic visualizations and the real world is a major advantage over schematic visualizations that has been demonstrated in empirical studies (Skulmowski & Rey, 2021b;Zanola et al, 2009). Zanola et al (2009) compared three visualization styles regarding their credibility ratings: a sketch style mimicking hand-drawn lines, a clean technical style lacking details, and a realistic style featuring even small details.…”
Section: Realism As a Condition For Cognitive And Emotional Effectsmentioning
confidence: 99%
“…In that study, a higher level of realism was associated with higher credibility ratings as indicated by differences between the ratings for these visualizations. In another study, Skulmowski and Rey (2021b) demonstrated that pictures of pathogens (bacteria) were rated as more credible than "toon" renderings of the same bacteria. Results such as these could be considered as evidence for a naive trust in realistic graphics in line with the assumptions of naive realism.…”
Section: Realism As a Condition For Cognitive And Emotional Effectsmentioning
confidence: 99%